An algorithm for finding time-cost trade-off pairs in generalised bi-criterion capacitated transportation problem. (2015) - Das, Atanu; Acharya, Debiprasad; Basu, Manjusri
In this paper, we consider generalised bi-criterion capacitated transportation problem. A solution procedure is presented to find the optimum transportation cost. Also, an algorithm is presented to find the optimum time-cost trade of pair in a generalised bi-criterion transportation problem giving the same priority to both time and cost. The algorithm identifies efficient time-cost trade-off pairs. Among the trade-off pairs we identify ideal solution. Then we reach the optimum trade-off pair having the minimum D1 -distance from the ideal solution. Finally, a numerical example is illustrated to support the algorithm.